A Novel Cellular Model to Study Angiotensin II AT2 Receptor Function in Breast Cancer Cells. (6th December 2011) - Rodrigues-Ferreira Rodrigues-Ferreira, Sylvie Sylvie; Morel Morel, Marina Marina; Reis Reis, Rosana I. Rosana I.; Cormier Cormier, Françoise Françoise; Baud Baud, Véronique Véronique; Costa-Neto Costa-Neto, Claudio M. Claudio M.; Nahmias Nahmias, Clara Clara
Abstract : Recent studies have highlighted the AT1 receptor as a potential therapeutic target in breast cancer, while the role of the AT2 subtype in this disease has remained largely neglected. The present study describes the generation and characterization of a new cellular model of human invasive breast cancer cells (D3H2LN-AT2) stably expressing high levels of Flag-tagged human AT2 receptor (Flag-hAT2). These cells exhibit high-affinity binding sites for AngII, and total binding can be displaced by the AT2-selective antagonist PD123319 but not by the AT1-selective antagonist losartan. Of interest, high levels of expression of luciferase and green fluorescent protein make these cells suitable for bioluminescence and fluorescence studies in vitro and in vivo . We provide here a novel tool to investigate the AT2 receptor functions in breast cancer cells, independently of AT1 receptor activation.